KEGIATAN PENANAMAN BIBIT SOLANUM LYCOPERSICUM DAN EDUKASI PEMASARAN DIGITAL BERSAMA KELOMPOK WANITA TANI BERKAH TANI MANDIRI DI DUSUN NANGGEWER DESA JELAT KECAMATAN BAREGBEG KABUPATEN CIAMIS - Futry Wella Fadillah; Meli Melinda; Novianti Fatimah Azzahra; Rini Nuraeni; Budi Setiadi (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
Tomato Planting and Digital Marketing Education activities for the Berkah Tani Mandiri Women's Farming Group in Nanggewer Hamlet, Jelat Village, carried out by a group of social and social sciences students from Galuh University, this activity lasted for approximately one month after observing the needs and conditions of the Women's Farmers Group. The aim of this activity is to have a positive impact and be able to provide education regarding the importance of digital marketing which is useful for increasing results and income for the Berkah Tani Mandiri Women Farming Group. This activity uses the planning, implementation, monitoring and evaluation stages method